Nanotechnological approaches in the treatment of schistosomiasis: an overview - Lucas Carvalho; Michelle Sarcinelli; Beatriz Patrício (Beilstein Journal of Nanotechnology, 2024)
Schistosomiasis causes over 200,000 deaths annually. The current treatment option, praziquantel, presents limitations, including low bioavailability and resistance. In this context, nanoparticles have emerged as a promising option for improving schistosomiasis treatment. Several narrative reviews have been published on this topic. Unfortunately, the lack of clear methodologies presented in these reviews leads to the exclusion of many important studies without apparent justification. This integrative review aims to examine works published in this area with a precise and reproducible method. To achieve this, three databases (i.e., Pubmed, Web of Science, and Scopus) were searched from March 31, 2022, to March 31, 2023. The search results included only original research articles that used nanoparticles smaller than 1 µm in the treatment context. Additionally, a search was conducted in the references of the identified articles to retrieve works that could not be found solely using the original search formula. As a result, 65 articles that met the established criteria were identified. Inorganic and polymeric nanoparticles were the most prevalent nanosystems used. Gold was the primary material used to produce inorganic nanoparticles, while poly(lactic-co-glycolic acid) and chitosan were commonly used to produce polymeric nanoparticles. None of these identified works presented results in the clinical phase. Finally, based on our findings, the outlook appears favorable, as there is a significant diversity of new substances with schistosomicidal potential. However, financial efforts are required to advance these nanoformulations.